OPTIMASI SUBSTRAT PERTUMBUHAN JAMUR LION'S MANE (HERICIUM ERINACEUS) DI DAERAH TROPIS - Dewi, Dora Silvia; Hartopo, Hartopo; Budiwan, Diah Wiyani (Institute of Computer Science (IOCS), 2024)
The Lion's Mane mushroom (Hericium erinaceus), known as lion's mane, is a mushroom that grows wild in European and North American countries, but currently this mushroom is starting to be cultivated artificially in tropical areas. However, it is necessary to modify the planting media, temperature and humidity so that this fungus can grow and develop well in tropical areas. The aim of this research was to see the growth rate of Lion's Mane mushroom mycelium on various substrates in the planting medium. The method used is descriptive qualitative research, namely by observing the growth of the Lion's Mane fungus on several media with different substrates. The research design was carried out by comparing the materials used in different ratios to obtain a suitable medium for the growth of Lion's Mane mushrooms. The results of this research are that from several types of nutritional sources used, rice flour and bran are the most ideal nutritional sources for the growth of Lion's Mane mushrooms. The use of a mixture of rice flour and bran showed the fastest mycelium growth, namely on day 4, while other nutritional sources such as a mixture of corn flour and bran showed rather slow mycelium growth, namely on day 10. Temperature and humidity also greatly influence the growth of the Lion's Mane fungus. Therefore, it is necessary to carry out further research by modifying the temperature and humidity suitable for the growth of the Lion's Mane fungus.